O meu pé de laranja lima : uma proposta metodológica a partir do texto verbal e do texto cinematográfico - Selória, Anadir Aparecida (2015)
This study proposes an intertextual work with the book "My Sweet Orange Tree" (1968), by Jose Mauro de Vasconcelos, and with the movie homonym (2012), directed by Marcos Bemstein. The main purpose is to develop didactic activities for the teachers to promote the development of literary literacy among 9th grade students from elementary schools, through comparative analysis of the song and the movie mentioned previously and also the change from verbal language into audio-visual verbal language. The reading activity, organized in a didactic unit, ends with an exhibition of the movie and also the activities about it. This research is based on Bakhtin's theory about the socio-interactionism ofthe discourse (1992, 1997, 2002); the theoretical approach proposed by Candido (1968, 2004) and Compagnon (2009); the cinematographic approach by 1-lohldfeld (1984) and Stam (1992); the Micheletti (2006) and Letfa researches (1996); and the literary literacy theory by Cosson (2014) and Zaponne (2014). The comparative analysis is directed and based on the Bakhtin's pillars of genres analysis (1992) - compositional construction, style and subject matter, adding to them the production conditions of theses writings; it was also influenced by Bourneuf and Ouellet contributions (1976) in regard to the compositional construction of the romance; by Faria's studies (1997) to focus on the author's style; particular information regarding cinema provided by Araujo (1995). The educational material has series activities, suggested by Rildo Cosson (2014), with explanations of specific contents supported by Soares (1997), Boumeuf and Ouellet (1976), Cegalla (1990) and Micheletti (2006). This research is justified because the relation between the romance and the movie is a way of catching students' attention for the reading, so that these midias retlect their reality, besides presenting the steps for this book reading an strategies to make them involved during the implementation of the proposal. lt is the result of the studies carried out at PROFLETRAS - Professional Mastery in Letters - Stricto Sensu modality that aims the preparation of educational resources to support Elementary School teachers. This ongoing formation fulfills the portuguese teachers in the search for strategies to develop their Wishes for reading, the literary literacy and teaching approaches that can make classes more interesting in such a way that till current needs of the students. So that the proposal can give students the opportunity to broaden their horizon when they compare the written text with the movie, teaching them the characteristics of the romance and the film so that it can improve their knowledge to observe and analyse other works adapted for films. Besides increasing the reading and writing skills it also enables the students to have a critical viewpoint of the different situations in their daily lives.